A General Two‐Step Strategy–Based High‐Throughput Screening of Single Atom Catalysts for Nitrogen Fixation. Issue 9 (13th December 2018) - Ling, Chongyi; Ouyang, Yixin; Li, Qiang; Bai, Xiaowan; Mao, Xin; Du, Aijun; Wang, Jinlan
Abstract: Electrocatalytic or photocatalytic N2 reduction holds great promise for green and sustainable NH3 production under ambient conditions, where an efficient catalyst plays a crucial role but remains a long‐standing challenge. Here, a high‐throughput screening of catalysts for N2 reduction among (nitrogen‐doped) graphene‐supported single atom catalysts is performed based on a general two‐step strategy. 10 promising candidates with excellent performance are extracted from 540 systems. Most strikingly, a single W atom embedded in graphene with three C atom coordination (W1 C3 ) exhibits the best performance with an extremely low onset potential of 0.25 V. This study not only provides a series of promising catalysts for N2 fixation, but also paves a new way for the rational design of catalysts for N2 fixation under ambient conditions. Abstract : A high‐throughput screening among N‐doped graphene–supported single atom catalysts is performed based on a general two‐step screening strategy. 10 promising candidates are selected from 540 systems, where W1 C3 presents the highest performance with an extremely low onset potential of 0.25 V.